Estudos sobre a síntese do ibuprofeno em condições de batelada e fluxo contínuo - Magalhães, Maria Flávia Assunção (2024)
Ibuprofen is a widely used anti-inflammatory drug for pain, inflammation and fever. Although there are several synthetic approaches to obtain this API, most of them involve reactions that have low efficiency using toxic, dangerous and expensive reagents. Therefore, a new methodology for the synthesis of ibuprofen was proposed, using innovative approaches such as electrosynthesis and photocatalysis in both batch and continuous flow conditions. Initially, the first proposed step starts from the compound isobutylbenzene, which is cheap and commercially available. A regioselective iodination in the para position was performed using “I+” generated in the anode chamber of a divided electrochemical cell. The best condition provided the first intermediate, paraiodoisobutylbenzene, in 90% yield in a 5:1:94 ratio of the ortho:meta:para regioisomers. The second step consisted of the photocatalyzed functionalization of paraiodoisobutylbenzene using an enol acetate to form 2-(4-isobutylphenyl)propanal. The parameters were explored using commercial starting materials (iodotoluene and isopropenyl acetate), which provided the photofunctionalization product in 52% yield. However, when the best reaction condition was applied with prop-1-enyl acetate for the synthesis of ibuprofen, a low yield (19%) was observed, in addition to obtaining a mixture of regioisomers, making the continuation of this synthetic route unfeasible. Other approaches aiming at the use of the aryl-iodo derivative were tested, however, without achieving the desired success.